Systematic Investigation of the Physical and Electrochemical Characteristics of the Vanadium (III) Acidic Electrolyte With Different Concentrations and Related Diffusion Kinetics - Jing, Minghua; Li, Chengjie; An, Xinyu; Xu, Zeyu; Liu, Jianguo; Yan, Chuanwei; Fang, Dawei; Fan, Xinzhuang (Frontiers in Chemistry, 2020)
Due to the lack of the systemic kinetic theory about the redox reaction of V(III)/V(II), the poor electrochemical performance of the negative process for vanadium flow battery limits the overall battery performance to a great extent. As the key influence factors of the electrode/electrolyte interfacial reactivity, the physico-chemical properties of the V(III) acidic electrolyte play an important role on the redox reaction of V(III)/V(II), hence a systemic investigation on the physical and electrochemical characteristics of the V(III) acidic electrolytes with different concentrations and the diffusion kinetics will be conducted in this work. It is found that the surface tension and viscosity of the electrolyte increase with the increasing V(III) concentration, while the corresponding conductivity presents an opposite trend. Meanwhile, both surface tension and viscosity change little with the increasing concentration of H2SO4, but the conductivity significantly increase, indicating that a lower V(III) concentration and a higher H2SO4 concentration are conducive to the ion transfer process. The electrochemical measurements further show that a higher V(III) concentration will facilitate the redox reaction of V(III)/V(II), while the increase of H2SO4 concentration only improve the ions transmission and has little effect on the electron transfer process. Furthermore, the diffusion kinetics of V(III) have been further studied with the cyclic voltammetry and chronopotentiometry. The results show that an elevated temperature facilitates the V(III)/V(II) redox reaction, and gives rise to the increased electrode reaction rate constant (ks) and diffusion coefficient (DV(III)) . On this basis, the diffusion activation energy (13.7 kJ•mol-1) and the diffusion equation of V(III) are provided to integrate the kinetic theory about the redox reaction of V(III)/V(II).